Mitophagy mediated by HIF-1α/FUNDC1 signaling in tubular cells protects against renal ischemia/reperfusion injury - Wenjun Zhang; Chao Guo; Yi Li; Hao Wang; Huabing Wang; Yingying Wang; Tingting Wu; Huinan Wang; Gang Cheng; Jiangwei Man; Siyu Chen; Shengjun Fu; et al. (Renal Failure)
Acute kidney injury (AKI) is associated with a high mortality rate. Pathologically, renal ischemia/reperfusion injury (RIRI) is one of the primary causes of AKI, and hypoxia-inducible factor (HIF)-1α may play a defensive role in RIRI. This study assessed the role of hypoxia-inducible factor 1α (HIF-1α)-mediated mitophagy in protection against RIRI in vitro and in vivo. The human tubular cell line HK-2 was used to assess hypoxia/reoxygenation (H/R)-induced mitophagy through different in vitro assays, including western blotting, immunofluorescence staining, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL), and reactive oxygen species (ROS) measurement. Additionally, a rat RIRI model was established for evaluation by renal histopathology, renal Doppler ultrasound, and transmission electron microscopy to confirm the in vitro data. The selective HIF-1α inhibitor LW6 reduced H/R-induced mitophagy but increased H/R-induced apoptosis and ROS production. Moreover, H/R treatment enhanced expression of the FUN14 domain-containing 1 (FUNDC1) protein. Additionally, FUNDC1 overexpression reversed the effects of LW6 on the altered expression of light chain 3 (LC3) BII and voltage-dependent anion channels as well as blocked the effects of HIF-1α inhibition in cells. Pretreatment of the rat RIRI model with roxadustat, a novel oral HIF-1α inhibitor, led to decreased renal injury and apoptosis in vivo. In conclusion, the HIF-1α/FUNDC1 signaling pathway mediates H/R-promoted renal tubular cell mitophagy, whereas inhibition of this signaling pathway protects cells from mitophagy, thus aggravating apoptosis, and ROS production. Accordingly, roxadustat may protect against RIRI-related AKI.